Nafkah Pasca Talak: Analisis Normatif dan Sosiologis atas Ketimpangan Ekonomi Perempuan - Khairuddin, Khairuddin (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
This study addresses the issue of post-divorce maintenance in Islamic law and national regulations in Indonesia, which is a significant concern for the protection of women's and children's rights after divorce. The research problem focuses on how the concept of post-divorce maintenance is regulated in Islamic law and the implementation of national regulations related to this maintenance. The aim of the research is to analyze the components of post-divorce maintenance, including mut’ah, iddah maintenance, and child support, as well as to evaluate the weaknesses and gaps in the existing laws. The method employed is library research, collecting and analyzing legal literature, official documents, and previous studies. The findings indicate that although there are clear provisions in the Compilation of Islamic Law and the Marriage Law, the implementation of these laws is often inconsistent, leaving many women without their rights. This study recommends the need for legal reform and increased legal awareness among women to ensure the protection of their rights post-divorce. [Penelitian ini membahas isu nafkah pasca talak dalam hukum Islam dan regulasi nasional di Indonesia, yang menjadi masalah penting dalam perlindungan hak-hak perempuan dan anak setelah perceraian. Rumusan masalah yang diangkat mencakup bagaimana konsep nafkah pasca talak diatur dalam hukum Islam dan bagaimana implementasi regulasi nasional terkait nafkah ini. Tujuan penelitian adalah untuk menganalisis komponen nafkah pasca talak, termasuk mut’ah, nafkah iddah, dan nafkah anak, serta mengevaluasi kelemahan dan kekosongan hukum yang ada. Metode yang digunakan adalah penelitian kepustakaan, dengan mengumpulkan dan menganalisis literatur hukum, dokumen resmi, dan penelitian sebelumnya. Temuan penelitian menunjukkan bahwa meskipun terdapat ketentuan yang jelas dalam Kompilasi Hukum Islam dan Undang-Undang Perkawinan, implementasi hukum sering kali tidak konsisten, dan banyak perempuan yang tidak mendapatkan hak-hak mereka. Penelitian ini merekomendasikan perlunya reformasi hukum dan peningkatan kesadaran hukum di kalangan perempuan untuk memastikan perlindungan hak-hak mereka pasca perceraian].